2020
DOI: 10.1155/2020/6085368
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review on the Attributes of Cluster Randomized Controlled Trials in Long-Term Care Facilities

Abstract: Cluster randomized trial design, where groups of participants are randomized instead of individual participants, is increasingly being used in long-term care research. The purpose of this review was to determine the characteristics of cluster randomized trials in long-term care facilities. A medical librarian conducted the literature search. Two independent reviewers reviewed each paper. Studies were included if the design was cluster randomized and participants were from long-term care facilities. For each in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Fourth, given the high prevalence of cognitive impairment among care home populations, 3 it is unsurprising to find that majority of studies obtained consent from residents and/or their proxies 12 . Nevertheless, consistent with the findings of a systematic review, 33 there remained a significant proportion of studies that excluded residents lacking capacity, probably due to complexities involved in the decision‐making process 34 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Fourth, given the high prevalence of cognitive impairment among care home populations, 3 it is unsurprising to find that majority of studies obtained consent from residents and/or their proxies 12 . Nevertheless, consistent with the findings of a systematic review, 33 there remained a significant proportion of studies that excluded residents lacking capacity, probably due to complexities involved in the decision‐making process 34 .…”
Section: Discussionmentioning
confidence: 87%
“…Having reviewed the literature, four systematic reviews were identified. Three [12][13][14] focused specifically on cluster-randomised trials, while one 15 Given that each country's social care system, and research governance structure and processes, shape the nature and conduct of feasible research, it was decided to limit the search to one jurisdiction and thus only include research that was subjected to UK research governance processes, that is ethical approval, research governance and regulatory approvals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation